Analysieren als Deuten/Wolf Schmid zum 60. Geburtstag - Fleishman, Lazar; Gölz, Christine; Hansen-Löve, Aage A. (Hamburg University Press, 2004)
This collection brings together the articles dedicated to the 60th birthday of Professor Wolf Schmid, one of the foremost literary scholars of our times who made a crucial contribution to a wide range of scholarly fields: narratology, poetics, history of Russian and Slavic literature, Pushkin and Dostoevsky. The contributors form a distinguished international group of prominent scholars whose essays in this volume further develop Wolf Schmid's narratological theory, shed new light on major works of literature and offer fascinating new insights into various periods of literary history.